2021
DOI: 10.1002/mp.14568
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of task‐based performance from five clinical DBT systems using an anthropomorphic breast phantom

Abstract: Purpose Digital breast tomosynthesis (DBT) is a limited‐angle tomographic breast imaging modality that can be used for breast cancer screening in conjunction with full‐field digital mammography (FFDM) or synthetic mammography (SM). Currently, there are five commercial DBT systems that have been approved by the U.S. FDA for breast cancer screening, all varying greatly in design and imaging protocol. Because the systems are different in technical specifications, there is a need for a quantitative approach for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 48 publications
(56 reference statements)
8
24
1
Order By: Relevance
“…This is not a trivial task as a realistic addition of the features requires a 3D localization within the Hyperia phantom. For instance, while other works have included microcalcification inserts in a single layer, [33][34][35] creating a pendant breast phantom requires a 3D placement of the specks layer by layer. A realistic implementation of the microcalcification cluster requires the positioning of the different specs in different layers.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a trivial task as a realistic addition of the features requires a 3D localization within the Hyperia phantom. For instance, while other works have included microcalcification inserts in a single layer, [33][34][35] creating a pendant breast phantom requires a 3D placement of the specks layer by layer. A realistic implementation of the microcalcification cluster requires the positioning of the different specs in different layers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted extensively to investigate the impact of AR on DBT through cascaded linear system modeling, [6][7][8][9] simulation studies, [10][11][12][13][14] physical phantom experiments, 7,11,[15][16][17][18][19][20] and evaluations using model observer [21][22][23][24][25][26][27][28][29][30] and human observer. [30][31][32][33][34][35][36] The impact of AR on the breast structural background in DBT has also been assessed. [37][38][39] Nosratieh et al investigated the slice sensitivity profiles (SSP) for different AR using subsets of projection images from a breast CT (bCT) scanner and showed that SSP improves with increasing AR.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted extensively to investigate the impact of AR on DBT through cascaded linear system modeling, 6 9 simulation studies, 10 14 physical phantom experiments, 7 , 11 , 15 20 and evaluations using model observer 21 30 and human observer 30 36 The impact of AR on the breast structural background in DBT has also been assessed 37 39 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach used a previously described physical anthropomorphic breast phantom with inserted microcalcification clusters of small size. 14 Although it is unclear if physical breast phantoms can be used to collect enough training data to train the denoising network, the approach could be used to evaluate networks previously trained on clinical data. The second approach used in silico computational methods with a previously developed anthropomorphic digital breast phantom 15 and GPU accelerated Monte-Carlo software 16 for simulating the imaging acquisition process.…”
Section: Introductionmentioning
confidence: 99%